2010
DOI: 10.1055/s-0030-1261931
|View full text |Cite
|
Sign up to set email alerts
|

A 9-Year Single Center Experience with Circumumbilical Ramstedt's Pyloromyotomy

Abstract: This is a large single-center retrospective study where, in the era of minimally invasive surgery, Ramstedt's pyloromyotomy via the circumumbilical approach has a low rate of complications and is a safe and feasible method to treat pyloric stenosis. The establishment of feeds soon after surgery minimizes the postoperative in-hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 18 publications
0
8
0
3
Order By: Relevance
“…Another 4 studies examined LOS as affected by early versus late feeding regimens. 3,4,13,14 Although early feeding was favored over late, the results were not statistically significant (MD −12.07; 95% CI, −32.46 to 8.31; I 2 94%; P = .25) (Fig 3). When a sensitivity analysis was performed on the 2 studies that classified "early feeding" as first feeding occurring at ≤4 hours, early feeding was still favored although not 5 …”
Section: Primary Outcome Analysis: Losmentioning
confidence: 94%
See 3 more Smart Citations
“…Another 4 studies examined LOS as affected by early versus late feeding regimens. 3,4,13,14 Although early feeding was favored over late, the results were not statistically significant (MD −12.07; 95% CI, −32.46 to 8.31; I 2 94%; P = .25) (Fig 3). When a sensitivity analysis was performed on the 2 studies that classified "early feeding" as first feeding occurring at ≤4 hours, early feeding was still favored although not 5 …”
Section: Primary Outcome Analysis: Losmentioning
confidence: 94%
“…Wheeler et al 14 also did not describe 3 of the 7 items, and although their method of sequence generation was assessed to be low risk, allocation concealment (unmarked, folded sheets) had a high risk of bias. In all 3 studies blinding was not possible for patients, personnel, or outcome assessors, and because outcomes may be influenced by this lack of blinding, these Table 2) The remaining 11 nonrandomized studies [1][2][3][4]9,13,[15][16][17][18]20 were assessed for methodological quality with the MINORS tool, 7 for which the majority of items were assessed similarly across studies (Table 1; see Supplemental Table 4 for greater detail). Few or no studies reported on the items "prospective collection of data" (reported in only 1 of 11 [9%] studies 16 ), "unbiased assessment of the study endpoint" (0 in 11 [0%] studies), and "prospective calculation of the study size" (0 in 11 [0%] studies).…”
Section: Methodological Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…However, it has been demonstrated that when IHPS is operated on in a specialized tertiary center, that the infection rate and hospital stay are significantly less [10].…”
Section: Discussionmentioning
confidence: 99%